2020
DOI: 10.1002/lpor.202000025
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz Emission on the Surface of a van der Waals Magnet CrSiTe3

Abstract: The van der Waals magnet CrSiTe 3 has captured immense interest because it is capable of retaining the long-range ferromagnetic order even in its monolayer form, thus offering potential use in spintronic devices. Bulk CrSiTe 3 crystal has inversion symmetry that is broken on the crystal surface with thickness of a few quintuple layers. Here, ultrafast terahertz (THz) emission spectroscopy and time resolved THz spectroscopy are employed to investigate the THz emission and the dynamics of photocarrier respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 42 publications
0
11
0
1
Order By: Relevance
“… CrSiTe 3 single crystals were grown using a self‐flux method, as described in detail in the study by Suo et al [ 28 ] The resulting plate‐like crystals, which measure ≈8 mm across, were characterized by room‐temperature X‐ray diffraction (XRD) using a Mo ( λ = 0.7107 Å) source in SuperNova single‐crystal XRD system. CrSiTe 3 crystallizes in the R 3 false¯ space group ( Figure a–c), consistent with the single‐crystal XRD data shown in Figure 1d, from which we determined the following lattice parameters: a = 6.7699 Å, b = 6.7699 Å, and c = 20.6825 Å ( α = β = 90 ° and γ = 120 °), in agreement with the study by Ouvrard et al [ 29 ] The layered structure of CrSiTe 3 can be seen in Figure 1b, where the ≈3.5 Å‐thick Cr−Si−Te quintuple layers with their Te terminations are separated by a ≈3.3 Å vdW gap.…”
Section: Methodsmentioning
confidence: 99%
“… CrSiTe 3 single crystals were grown using a self‐flux method, as described in detail in the study by Suo et al [ 28 ] The resulting plate‐like crystals, which measure ≈8 mm across, were characterized by room‐temperature X‐ray diffraction (XRD) using a Mo ( λ = 0.7107 Å) source in SuperNova single‐crystal XRD system. CrSiTe 3 crystallizes in the R 3 false¯ space group ( Figure a–c), consistent with the single‐crystal XRD data shown in Figure 1d, from which we determined the following lattice parameters: a = 6.7699 Å, b = 6.7699 Å, and c = 20.6825 Å ( α = β = 90 ° and γ = 120 °), in agreement with the study by Ouvrard et al [ 29 ] The layered structure of CrSiTe 3 can be seen in Figure 1b, where the ≈3.5 Å‐thick Cr−Si−Te quintuple layers with their Te terminations are separated by a ≈3.3 Å vdW gap.…”
Section: Methodsmentioning
confidence: 99%
“…This is in good accordance with the extremely high sensitivity of Cr 2 Ge 2 Te 6 to external low‐intensity photonic field. [ 38 ] Unlike other THz sources based on 2D materials, [ 7 , 8 , 9 ] this unique THz‐MRS takes full advantage of the inter‐layered breathing phonons and achieves highly efficient monochromatic THz radiations with stimulation of low‐energy THz pulse. This mechanism is of great practical interests, such as monochromatic THz laser, integrated gain‐type monochromatic THz filter, key relay components in photonic communication, etc.…”
Section: Resultsmentioning
confidence: 99%
“…[7] Under the excitation of strong infrared pulses, Suo et al proposed a new THz emitter based on the shift current occurring on the inversion-broken surface of layered CrSiTe 3 crystal. [8] With the aid of laser-excited surface plasmon on a gold substrate, Bahk et al observed an enhanced THz emission from the singlelayered graphene. [9] In the majority of these studies, THz radiation based on 2D vdWs materials are originating from photoconductive effect, optical rectification, and laser-induced plasma, which all belong to the fermion (electron) catalog and generally bring broadband THz emission with low conversion efficiency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The photocurrent-induced terahertz emission in monolayer TMDs should be related to the pump photon polarization in the shift current, photo-Dember current, and drift current. To distinguish these different origins of the photocurrent-induced terahertz emission in the WSe 2 /Si heterostructure, the polarization and incident angle dependence of the terahertz emission are investigated, as shown in Figure . To eliminate the disturbance of the valley transition process in WSe 2 , a pump photon energy of 2.58 eV is used to measure the polarization dependence of the terahertz emission in WSe 2 /Si, Si, and monolayer WSe 2 .…”
mentioning
confidence: 99%